(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In this article one tries to analyze the complexity of the Law. And MichelBastit´s thought takes as a reference. The different conceptions of the Law positivists, antiformalists, etc.) they arrange and are interpreted depending on a morewide and comprenhensive conception of the Law, this is, a hermeneutics conceptionof the Law. The contemporary hermeneutics, the interpretations of the law and theanalogy will be the steps that drive us to descipher a conception of the Law, that ofBastit, which tries to harmonize the form and the purpose in the Law.